Odpowiedzi

Najlepsza Odpowiedź!
  • Użytkownik Zadane
2010-02-23T09:48:24+01:00
A) a(a+b)+a(a-b)+b(b+a)+b(b-a)=a²+ab+a²-ab+b²+ab+b²-ab=2a²+2b²
b) 8x(x+y)-2y(y-x)+½(6x²+8x²)-2(y²+5xy)=
=8x²+8xy-2y²+2xy+3x²+4x²-2y²-10xy=15x²-4y²
2010-02-23T09:50:22+01:00
A) a(a+b)+a(a-b)+b(b+a)+b(b-a) = a² + ab + a² - ab + b² + ab + b² - a² = a² + ab + 2b²
b) 8x(x+y)-2y(y-x)+½(6x²+8x²)-2(y²+5xy) = 8x² + 8xy - 2y² + 2xy + 3x² + 4x² - 2y² - 10xy = 15x² - 4y²
2010-02-23T09:54:07+01:00
A) a(a+b)+a(a-b)+b(b+a)+b(b-a) = a²+ab+a²-ab+b²+ab+b²-ab = 2a²+2b²

b) 8x(x+y)-2y(y-x)+½(6x²+8x²)-2(y²+5xy) = 8x²+8xy-2y²+2xy+3x²+4x²-2y²-10xy = 15x²-4y²

Pozdrawiam ;) Mam nadzieję, że pomogłam :)